YAP plays a protective role in T-2 toxin-induced inhibition of chondrocyte proliferation and matrix degradation. (August 2022) - Li, Hao-Nan; Jin, Bai-Ming; Hua Zhang,; Le-Le Liu,; Meng-Yuan Li,; Xiu-Juan Zheng,; Xu-Ying Li,; Wang, Ke-wei
Abstract: Previous research has shown that T-2 toxin can damage cartilage, resulting in a disease phenotype similar to osteoarthritis. The precise molecular mechanism by which T-2 toxin causes chondrocyte injury, however, is unknown. The purpose of this study was to look into the role of YAP in T-2 toxin-induced rat chondrocyte injury. Based on research results, T-2 toxin decreased the levels of collagen II and PCNA while increasing the expression of matrix metalloproteinase MMP13. These findings supported the T-2 toxin's detrimental effect on chondrocytes. YAP's role in T-2 toxin-induced chondrocyte injury was also investigated. Total YAP and related nuclear proteins were found to decrease as the concentration of T-2 toxin increased. While PYAP expression was not significantly altered in response to T-2 toxin, the PYAP/YAP ratio decreased as the T-2 toxin concentration increased, implying that the HIPPO signaling pathway was activated. Furthermore, the YAP-specific inhibitor Verteporfin was used to investigate the role of YAP in T-2 toxin-induced chondrocyte injury. YAP inhibition increased MMP13 expression while decreasing COL2 and PCNA levels. In summary, the current study found that T-2 toxin decreased the levels of COL2 and PCNA while increasing the expression of MMP13 in chondrocytes after inhibiting YAP, providing a new insight into the mechanism of T-2 toxin-induced cartilage damage. Graphical abstract: Schematic diagram for the molecular mechanism of YAP in T-2 toxin-induced chondrocyte injury. T-2 toxin phosphorylates YAP in the cytoplasm and inhibits the entry of YAP into the nucleus for binding to transcription factors, resulting in the upregulation of MMP13, the downregulation of Collagen II, the reduction of PCNA, and ultimately chondrocyte damage. Image 1 Highlights: Yes-related protein is the most critical effector of HIPPO signaling pathway to regulate proliferation and apoptosis. Nuclear expression of Yes-related proteins was decreased when chondrocytes were treated with T-2 toxin. T-2 toxin stimulates the expression of MMP 13 and degradation of collagen type II through Yes-related protein. T-2 toxin inhibits chondrocyte proliferation, perhaps by suppressing the expression of Yes-related protein.